The Organization of the Albanian Education System and the Status of the Italian Language in the Period 1920-1944 - Muceku, Albana (European Journal of Multidisciplinary Studies, 2017)
The article in question reflects in a summarized way the organization of the Albanian education system in the years 1920-1944, as well as the status and position of the Italian language in this system, during that period. The existing interest in the Italian language in Albania is closely related to the old relations the two countries have had. Notwithstanding fluctuations that such relations have undergone, this connection never disappeared. This long-standing relationship is the result of good neighborly ties built and maintained naturally by the people of the two countries. The wish of Ahmet Zog (the king in power at the time) and his cabinet was to create a state based on Western European models. Therefore, there was wide cooperation, not just in the economic and diplomatic field, but also in other areas, particularly concerning relations with the Italian state which at that period was the main supporter of Albania, and also with other western countries. Western European models served to establish and strengthen the Albanian state which had just been taking shape trying to follow the model European-leaning states. Based on historical facts, during the period 1920-1944, the Albanian educational system underwent numerous changes. These changes enabled the Albanian education system to take the form of a more unified and more developed model. The influence of the Italians in Albania was obvious in different fields such as the commercial, economic and social sectors. Given that this period was characterized by the intensification of the relations between Italy and Albania, it was inescapable that this relationship would be manifested also in the field of education. Therefore, this paper intends to demonstrate through historical facts extracted from press articles and publications of the time, the changes to the Albanian education system in the years 1920-1944, as well as the status of the Italian language during this period.Keywords: Albanian education, Italian language, organization, influence, relations.